Apiculture Activities Throughout The Bitlis County - Cagliyan, Ayse (Istanbul Univ, Fac Letters, Dept Geography, 2015)
Apiculture holds a significant importance for our country, that its economy largely depended on agriculture and animal husbandry along with its trend of rural to urban migration is higher. It is apiculture that enables easiest provide of work and income to the citizens inhabited throughout the villages in hilly relief that preventing their agricultural production but presenting a large area of pasture. Apiculture is an economic activity to be managed without serious requirement of capital by every single person in community that also reaps a profit in a short while. In terms of these characteristics that provide cheap employment, Apiculture is one of the leading economic activities of today. By the fact that the Bitlis County corresponds a pretty hilly area, it also holds the most suitable ecological specialties in terms of apiculture. Hilly and mountainous areas at the southeastern sector of Bitlis, are densely used by both local and even itinerant beekeepers especially in blossom period of thyme and astragalus. Center, Hizan and Mutki districts are the areas that these activities have mostly being performed.
Keywords: Bitlis; Hizan; Apiculture; Honey Production; Itinerant beekeping